Effects of pregnancy-induced hypertension on early-onset neonatal thrombocytopenia - Ye, Meiling; Zhou, Cailing; Li, Lu; Wang, Lizhen; Zhang, Meixian (BMC pregnancy and childbirth, 2025)
Gestational hypertension and preeclampsia are potentially linked to similar pathophysiological processes. Maternal preeclampsia increases the occurrence of early-onset neonatal thrombocytopenia. We hypothesized that maternal gestational hypertension may impact the incident early-onset neonatal thrombocytopenia. We included 538 neonates, comprising 318 and 220 neonates born to healthy mothers and those with pregnancy-induced hypertension. The minimum platelet count within 72 h of birth was recorded for these neonates. The incidence of early-onset thrombocytopenia in neonates in relation to maternal gestational hypertension, preeclampsia, and health status was evaluated. Logistic regression analysis was conducted to assess the relationship between maternal gestational hypertension and the risk of early-onset neonatal thrombocytopenia. The incidence of early-onset thrombocytopenia was significantly higher in neonates born to mothers with preeclampsia than in those born to mothers with gestational hypertension or healthy mothers. Significant differences were observed among the three groups (30.0% vs. 13.3% vs. 7.9%, p < 0.001). Maternal gestational hypertension (OR = 2.79, 95%CI 1.19-6.54) increased the risk of early-onset neonatal thrombocytopenia when compared to healthy mothers. Maternal gestational hypertension increases the occurrence of early-onset neonatal thrombocytopenia. Therefore, we recommend conducting platelet count screening at the early stages of neonates of mothers with gestational hypertension.